2002
DOI: 10.1007/bf02573894
|View full text |Cite
|
Sign up to set email alerts
|

Placement of self-expanding metal stents for acute malignant large-bowel obstruction: A collective review

Abstract: In our experience with 26 patients who developed a complete bowel obstruction as a consequence of a malignant tumor, placement of colonic stents to achieve immediate nonoperative decompression proved to be both safe and effective. Subsequent elective resection was accomplished in the majority of resectable cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(15 citation statements)
references
References 25 publications
1
12
0
2
Order By: Relevance
“…In recent years, some authors have reported favorable results for non-surgical relief of acute malignant colonic obstruction by placing an uncovered, self-expandable metallic stent (11-13, 16-19). The technical and clinical success rates of our study are comparable to other series, which varied between 80% and 100% (11-21, 24-28). The site of the lesion influences the technical success rate, with rectosigmoid lesions being easier to treat than transverse colon lesions.…”
Section: Discussionsupporting
confidence: 86%
“…In recent years, some authors have reported favorable results for non-surgical relief of acute malignant colonic obstruction by placing an uncovered, self-expandable metallic stent (11-13, 16-19). The technical and clinical success rates of our study are comparable to other series, which varied between 80% and 100% (11-21, 24-28). The site of the lesion influences the technical success rate, with rectosigmoid lesions being easier to treat than transverse colon lesions.…”
Section: Discussionsupporting
confidence: 86%
“…A review by Watt et al found median complication rates of stent migration 11%, perforation 4.5%, and tumour overgrowth 12% [12]. Clinical success is usually quoted at a rate of 85–100% [1, 8, 12, 13] with mortality between 0 and 2%. This study had a primary perforation rate of 0% in line with the literature, but we had an overall mortality of 2/37 (5%) when restented patients were taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Open surgery for acute bowel obstruction due to malignant left-sided colonic tumors is associated with a high chance of stoma creation as well as increased mortality and morbidity. For these reasons, during the past two decades, these tumors have been increasingly treated with endoscopic decompression at the initial phase and then definitive laparoscopic excision (1).…”
Section: Introductionmentioning
confidence: 99%